mMCP7, a Mouse Ortholog of δ Tryptase, Mediates Pelvic Tactile Allodynia in a Model of Chronic Pelvic Pain - Pattabiraman, Goutham; Liu, Zhiqiang; Paul, Madhumita; Schaeffer, Anthony J.; Thumbikat, Praveen (Frontiers in Pain Research, 2022)
Chronic prostatitis/Chronic pelvic pain syndrome (CP/CPPS) is a condition that affects a large number of men and has unknown etiology. We have previously demonstrated the presence of elevated levels of mast cell tryptase in expressed prostatic secretions (EPS) of CP/CPPS patients. In a murine model of CP/CPPS, we showed tryptase and its cognate receptor PAR2 as critical to the development of pelvic pain and lower urinary tract symptoms. Here, we extend these observations to demonstrate that an isoform of tryptase called delta (δ)-tryptase, is elevated in the EPS of patients with CP/CPPS and is correlated with pelvic pain symptoms. Using an Escherichia coli (CP1) -induced murine model of CP/CPPS, we demonstrated a differential response in C57BL/6J and NOD/ShiLtJ mice, with C57BL6/J mice being resistant to an increase in pelvic tactile allodynia, despite having equivalent levels of activated mast cells in the prostate. Activated tryptase+ve mast cells were observed to be in closer apposition to PGP9.5+ve nerve fibers in the prostate stroma of NOD/ShiLtJ in comparison to C57BL/6J mice. The mouse ortholog of δ-tryptase, mouse mast cell protease 7 (mMCP7) has been reported to be unexpressed in C57BL/6J mice. We confirmed the absence of mMCP7 in the prostates of C57BL/6J and its presence in NOD/ShiLtJ mice. To evaluate a role for mMCP7 in the differential allodynia responses, we performed direct intra-urethral instillations of mMCP7 and the beta (β)-tryptase isoform ortholog, mMCP6 in the CP1-infection model. mMCP7, but not mMCP6 was able to induce an acute pelvic allodynia response in C57BL/6J mice. In-vitro studies with mMCP7 on cultured mast cells as well as dissociated primary neurons demonstrated the ability to induce differential activation of pain and inflammation associated molecules compared to mMCP6. We conclude that mMCP7, and possibility its human ortholog δ-tryptase, may play an important role in mediating the development of pelvic tactile allodynia in the mouse model of pelvic pain and in patients with CP/CPPS.